Secondary prevention therapies following percutaneous coronary intervention or acute coronary syndrome in patients with diabetes mellitus - Planchat, Arnaud; Gencer, Baris; Degrauwe, Sophie; Musayeb, Yazan; Roffi, Marco; Iglesias, Juan F. (Frontiers in Cardiovascular Medicine, 2024)
Diabetes mellitus (DM) promotes atherosclerosis, leading to increased risk for cardiovascular morbidity and mortality. Diabetics represent a challenging subset of patients undergoing percutaneous coronary intervention (PCI) or who have experienced an acute coronary syndrome (ACS), a subset characterized by higher rates of recurrent ischemic events compared with non-diabetics. These events are caused by both patient-related accelerated atherosclerotic disease progression and worse stent-related adverse clinical outcomes translating into a higher risk for repeat revascularization. In addition, DM is paradoxically associated with an increased risk of major bleeding following PCI or an ACS. Secondary prevention therapies following PCI or an ACS in diabetic patients are therefore of paramount importance. This mini review focuses on the currently available evidence regarding short- and long-term secondary prevention treatments for diabetic patients undergoing PCI or who have experienced an ACS.